2015
DOI: 10.1073/pnas.1509119112
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoregulatory protein 14-3-3 facilitates SAC1 transport from the endoplasmic reticulum

Abstract: Most secretory cargo proteins in eukaryotes are synthesized in the endoplasmic reticulum and actively exported in membrane-bound vesicles that are formed by the cytosolic coat protein complex II (COPII). COPII proteins are assisted by a variety of cargo-specific adaptor proteins required for the concentration and export of secretory proteins from the endoplasmic reticulum (ER). Adaptor proteins are key regulators of cargo export, and defects in their function may result in disease phenotypes in mammals. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…To exit the ER after serum starvation, mammalian Sac1 is thought to oligomerize via its N‐terminal LZ motif and interact with the COPII subunit Sec23 (Figure C). Sac1 incorporation into COPII vesicles requires the cytosolic adaptor protein 14‐3‐3, which directly binds a minimal ER sorting motif in SacN (L146S147) that lies within a 7 amino acid sequence (RLSNTSP) similar to consensus 14‐3‐3 binding sites (Figure D). Because 14‐3‐3 proteins can also bind the COPII sorting subunit Sec24, 14‐3‐3 dimers may act as a bridge to concentrate Sac1 at ER exit sites and facilitate its integration into COPII‐vesicles destined for the Golgi .…”
Section: Sac1 Function In Different Intracellular Compartmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exit the ER after serum starvation, mammalian Sac1 is thought to oligomerize via its N‐terminal LZ motif and interact with the COPII subunit Sec23 (Figure C). Sac1 incorporation into COPII vesicles requires the cytosolic adaptor protein 14‐3‐3, which directly binds a minimal ER sorting motif in SacN (L146S147) that lies within a 7 amino acid sequence (RLSNTSP) similar to consensus 14‐3‐3 binding sites (Figure D). Because 14‐3‐3 proteins can also bind the COPII sorting subunit Sec24, 14‐3‐3 dimers may act as a bridge to concentrate Sac1 at ER exit sites and facilitate its integration into COPII‐vesicles destined for the Golgi .…”
Section: Sac1 Function In Different Intracellular Compartmentsmentioning
confidence: 99%
“…Sac1 incorporation into COPII vesicles requires the cytosolic adaptor protein 14‐3‐3, which directly binds a minimal ER sorting motif in SacN (L146S147) that lies within a 7 amino acid sequence (RLSNTSP) similar to consensus 14‐3‐3 binding sites (Figure D). Because 14‐3‐3 proteins can also bind the COPII sorting subunit Sec24, 14‐3‐3 dimers may act as a bridge to concentrate Sac1 at ER exit sites and facilitate its integration into COPII‐vesicles destined for the Golgi . For Golgi exit and transport back to the ER following serum stimulation, a dilysine motif (KEKIDD) at the Sac1 C‐terminus is required for COPI‐vesicle transport (Figures C and C).…”
Section: Sac1 Function In Different Intracellular Compartmentsmentioning
confidence: 99%
“…These proteins not only facilitate the selection of their specific cargos into different vesicles, but they also act as adaptors of cargo proteins, allowing interaction with COPII coat proteins and modulating the size of transport vesicles. Recently, 14-3-3, a phosphoregulatory protein, has been shown to act as an adaptor protein for a phosphatidylinositol 4-lipid phosphate, SAC1 (24). SAC1 exits the ER in a COPII-dependent manner; however, its efficient packaging into COPII vesicles requires 14-3-3 protein (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 14-3-3, a phosphoregulatory protein, has been shown to act as an adaptor protein for a phosphatidylinositol 4-lipid phosphate, SAC1 (24). SAC1 exits the ER in a COPII-dependent manner; however, its efficient packaging into COPII vesicles requires 14-3-3 protein (24). Utilizing a variety of cell biological and biochemical techniques, it has been shown that the export .…”
Section: Discussionmentioning
confidence: 99%
“…In growth factor-deprived cells, SAC1 oligomerizes and traffics from the ER to the Golgi, depleting Golgi PtdIns(4)P, thus interfering with secretory trafficking [9]. Since SAC1 is exported from the ER into COPII vesicles at similar levels in starved and non-starved cells, growth factor-dependent ERGolgi trafficking of SAC1 is likely regulated at the level of Golgi retrieval [10]. Stimulation with growth factors such as FGF and PDGF activates the p38/MAPK pathway, triggering dissociation of SAC1 oligomers and COPI-mediated retrograde trafficking of SAC1 to the ER.…”
Section: Growth Factor Signaling Controls Golgi Secretory Functionmentioning
confidence: 99%